Factorial Structure of Job Satisfaction for Female Employees Working in the Private Sector (shopping malls in Tabuk) - Almehdawi, Abdullah Mohamed; Alanazi, Mai Ali (Journal of Educational and Psychological Sciences, 2022)
This study aimed to develop a scale that measures the job satisfaction level in female employees working at shopping malls. The job satisfaction scale was constructed and the final version of the scale consisted of (37) items distributed into five dimensions: work environment, roles and duties, supervision and follow up, human relations, and finally income and incentives. The study adopted the descriptive approach and the scale was administrated to a simple and random sample that consisted of (252) female employees. Results were analyzed using (SPSS, and AMOS). The study used factor analysis validity to verify the construct validity, convergent validity, and discriminant validity and the indicators were strong. Reliability was verified using Cronbach's Alpha, reliability factor of the edited model ranged between (0.87 and 0.94), although the total reliability factor was (0.97). The results demonstrated that: the job satisfaction score was high in the five criteria in general according to the pentagonal scale used, the average response of the sample in all dimensions ranged between (2.85- 3.98) and it was as follows: human relations, work environment, supervision and follow up, then roles and duties, and lastly income and incentives. In light of these results the current study provided a number of recommendations, the most important of which is: to develop an inspection visiting plan by the Ministry of Labor to ensure the satisfaction of female employees and to monitor the work flow specially after the application of new work regulations, also to encourage the institutions to pay more attention to the income and incentives aspect and provide better proposals and services to the female employees.
Keywords: Factorial Structure; Job Satisfaction; Private Sector; shopping malls